Art et culture à Ramallah dans les Territoires palestiniens occupés (TPO): Entre patrimoine, revendications politiques et développement territorial - Pauline Bosredon; Sophie Gravereau; Marie-Thérèse Grégoris; Anissa Habane (Belgeo)
Studying the relationship between culture and space in the occupied Palestinian territories (OPT) invites us to interrogate the relationship between art, heritage, political claims and territorial development: the recent history of the West Bank has demonstrated the role of the artistic engagement and cultural development of the political stakeholders in the reconquest of the old city centers and in the affirmation of Palestinian identity. The aim of this scientific paper is to understand the mechanisms through which cultural actors, in the broad sense, seek to create a new cultural centrality in the heart of the oPt.